SUSTAINABILITY REPORT DISCLOSURE: A GOOD CORPORATE GOVERNANCE MECHANISM - Sari Mujiani; Juardi; Ainun Nadhifah (FEB-UP Press, 2021)
A sustainability report is a document that provides internal and external stakeholders with corporate responsibility reports on social, economic, and environmental aspects of an organization's or company's success in order to achieve sustainable growth. The aim of this analysis is to see how good corporate governance affects sustainability reports. Institutional ownership, an independent board of commissioners, and an audit committee are the study's independent variables. A quantitative analysis approach was used in this study. The sample was taken using a technique known as purposive sampling. The sample used in this study is a legitimate company listed on the Indonesia Stock Exchange that publishes sustainability and financial reports on a regular basis for the 2016-2018 period, with a total of 16 firms. Institutional ownership and the audit committee had a positive impact on the sustainability study, according to the findings. The sustainability report has no impact on the independent board of commissioners. These findings suggest that the presence of an independent board of commissioners has had no substantial impact on the company's decision to disclose its sustainability report.